2021
DOI: 10.21608/jhiph.2021.206186
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C among Hospital Personnel and Patients at a General Hospital in Kafr Elsheikh Governorate, Egypt

Abstract: Background: To fight against hepatitis C virus (HCV) epidemic in Egypt, it is crucial to understand the actual HCV situation. Hospitals have been accused as being an epicenter for sustained HCV spread in Egypt. Health care workers (HCWs) as well as patients admitted to hospitals are at special risk of acquiring HCV infection compared to the general population. Aim: To compare between the occurrence of hepatitis C in hospital personnel and patients at a general hospital in Kafr Elsheikh Governorate with referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Rural residents were approximately three to four times more likely to test HCV positive than urban residents (OR=2.679, p=0.019; OR=4.442, p=0.004, respectively). 5 The study by Anwar et al, 2021, 8 of patients and HCWs at Ain Shams University Hospitals in Cairo, found similar observation that patients and HCWs living in rural areas outside of Cairo had more significant proportions of HCV antibodies (11.11% vs. 7.32%, p=0.5, and 30.54% vs. 14.41%).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Rural residents were approximately three to four times more likely to test HCV positive than urban residents (OR=2.679, p=0.019; OR=4.442, p=0.004, respectively). 5 The study by Anwar et al, 2021, 8 of patients and HCWs at Ain Shams University Hospitals in Cairo, found similar observation that patients and HCWs living in rural areas outside of Cairo had more significant proportions of HCV antibodies (11.11% vs. 7.32%, p=0.5, and 30.54% vs. 14.41%).…”
Section: Discussionmentioning
confidence: 73%
“…Our findings are consistent with those of another study, demonstrated a correlation between anti-HCV positive and hepatitis risk factors, including sociodemographic, occupational, and other factors. 5 That study found that anti-HCV was significantly more prevalent in older age groups (17.3% vs. 6.6%, p=0.029) than in younger age groups. Regarding gender, 10% of females and 7% of males were anti-HCV positive.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations